Analisis Tingkat Keberhasilan Penerapan Restorative Justice terhadap Tindak Pidana Ringan di Polres Bangka Tengah - Tegar Tegar; Jeby Fhahira; Zaldia Fudiani; Riansyah; Dwi Haryadi (Jurnal Hukum Lex Generalis, 2025)
This study is motivated by the significance of developing the restorative justice concept as a reform in criminal justice to resolve cases through a non-litigation approach involving offenders, victims, families, and the community. It aims to analyze the implementation of restorative justice by the Central Bangka Police based on Police Regulation Number 8 of 2021. Employing a descriptive qualitative approach, data were collected from various sources between January 2024-May 2025 on minor criminal cases both successfully and unsuccessfully handled using restorative justice. Findings indicate the concept effectively restores social relationships and ensures legal protection for all parties involved.